Sustainable management of land resources : an Indian perspective - Chaturvedi, Arun; Obi Reddy, G. P.; Patil, N. G. (Oakville, ON ; Waretown, NJ : Apple Academic Press, 2017)
"The depletion of land resources is one of the greatest challenges for mankind in this millennium. Shrinking land resources, weather aberrations, deterioration of land quality, and the globalization and liberalization of market economies have become intertwined to influence the sustainable management of land resources and land use plans. This important volume, Sustainable Management of Land Resources: An Indian Perspective, addresses these challenges. This comprehensive volume, covering important research, much of it gathered with the use of new technology, tools, and applications, is organized into four sections: (add bullets)land resource inventory and characterizationgeospatial technologies in land resource mapping and managementsoil nutrient status and management land use planning and livelihood securityThe volume looks at how scientists translate their knowledge and experience in sustainable land resources and management into implementable policy decisions, with a particular focus on India. Since India is an agrarian economy, the land resources assume a very critical role affecting the livelihood of a vast majority of populace in the country. The information gathered--and the methods by which it is gathered--is applicable globally. This comprehensive publication will be highly useful for the researchers, academicians, extension workers, policymakers, planners, officials of land resources survey, planning and management institutions/agencies/departments, and others. "--Provided by publisher.
chapter 1 Land Resource Inventory, Mapping and Management: An Indian Perspective / G. P. Obi Reddy -- chapter 2 Soil Management and Land Use Planning: An Indian Perspective / N. G. Patil -- part Part I: Land Resource Inventory and Characterization -- chapter 3 Land Resource Inventory and Evaluation for Agricultural Land Use Planning in Semi-Arid Ecosystem of Western India / B. P. Bhaskar -- chapter 4 Characterization and Classification of Soils of the Purna Valley in the Semi-Arid Region of Central India / R. K. Naitam -- chapter 5 Evaluation of Shrink-Swell Soils in Semi-Arid Regions of Central India for Soil Resource Management and Sustainable Agriculture / Prakash R. Kadu -- chapter 6 Mapping and Characterization of Salt Affected Soils for Reclamation and Management: A Case Study from the Trans-Gangetic Plains of India / A. K. Mandal -- chapter 7 Characterization of Coastal Soils for Enhancement of Productivity and Livelihood Security: A Case Study from the Coastal Plains of West Bengal, India / S. K. Gangopadhyay -- chapter 8 Assessment of Land Degradation Vulnerability: A Case Study from Part of Western Ghats and the West Coast of India / K. S. Anil Kumar -- chapter 9 Major and Trace Element Geochemistry in Ferruginous Soils Developed Under the Hot Humid Malabar Region, India / P. N. Dubey -- part Part II: Geopatial Technologies in Land Resource Mapping and Management -- chapter 10 Geospatial Tools and Techniques in Land Resources Inventory / Suresh Kumar -- chapter 11 Morphometric Analysis Using GIS Techniques: A Case Study from the Basaltic Terrain of Central India / Nisha Sahu -- chapter 12 Digital Terrain Analysis and Geomorphological Mapping Using Remote Sensing and GIS: A Case Study from Central India / B. S. Manjare -- chapter 13 Time Series Satellite Data and GIS for Crop Acreage Estimation: A Case Study from Central India / A. R. Pimpale -- chapter 14 Assessment of Gross Primary Productivity in the Semi Arid Agricultural Region of Central India Using Temporal MODIS Data / Jugal Kishore Mani -- chapter 15 Land Suitability Evaluation for Soybean Using Temporal Satellite Data and GIS: A Case Study from Central India / Nirmal Kumar -- chapter 16 Geospatial Technologies in Development of Soil Information System and Prototype GeoPortal / G. P. Obi Reddy -- part Part III: Soil Nutrient Status and Management -- chapter 17 Geo-Referenced Soil Fertility Monitoring for Optimized Fertilizer Use: A Case Study from the Semi-Arid Region of Western India / R. N. Katkar -- chapter 18 Assessment of Soil Fertility Status in Soybean Growing Soils: A Case Study from the Semi-Arid Region of Central India / A. S. Gajare -- chapter 19 Soil Acidity and Poor Nutrient Status: Emerging Issues for Agricultural Land Use Planning in Jamtara District of Jharkhand / A. K. Sahoo, S. K. Singh, D. C. Nayak, S. Mukhopadhyay, T. Banerjee, D. Sarkar, A. K. Sarkar, B. K. Agarwal, D.K. Shahi, and Arvind Kumar -- chapter 20 Spatial Distribution of Available Nutrients in Aswagandha (Withania somnifera) Grown Soils of Farmers$1 (BFields in Andhra Pradesh /s B. Vajantha -- chapter 21 Management of Sodic Black Calcareous Soils: A Case Study from Central India / A. O. Shirale -- chapter 22 Impact of Land Configuration and Integrated Nutrient Management on Productivity of Rainfed Cotton in Vertisols of Central India / V. V. Gabhane -- chapter 23 Impact of Tank Silt on Soil Quality and Crop Productivity in Rainfed Areas: A Case Study from Central India / V. K. Kharche -- chapter 24 Impact of Treated Domestic Sewage Water Irrigation on Soil Properties, Maize Yield and Plant Uptake: A Case Study from Nagpur City, Central India / A. R. Mhaske -- part Part IV: Land Use Planning and Livelihood Security -- chapter 25 Status of Land Use Planning in India / N. G. Patil -- chapter 26 Land Resource Inventory Towards Village-Level Agricultural Land Use Planning / V. Ramamurthy -- chapter 27 A Decade of Bt Cotton in India: Land Use Changes and Other Socio-Economic Consequences / M. V. Venugopalan -- chapter 28 Land Evaluation for Rainfed Cotton: A Case Study from Central India / Dhanashree Pable -- chapter 29 Nutrient Optima-Based Productivity Zonality and Rationale of Fertilizer Use in Citrus / A. K. Srivastava -- chapter 30 Impact of Mahatma Gandhi NREGS on Land Use Pattern and Natural Resource Management in the Drought-Prone Rayalaseema Region of Andhra Pradesh, India / V. Suresh Babu.
Keywords: Land use -- India; Land use mapping -- India; Land degradation -- Control -- India